Rational design of three-layered TiO2 @carbon@MoS2 hierarchical nanotubes for enhanced lithium storage - Wang, Sibo (2020)
Here we demonstrate the rational design and synthesis of three-layered TiO2 @carbon@MoS2 hierarchical nanotubes for anode applications in lithium-ion batteries (LIBs). Through an efficient step-by-step strategy, ultrathin MoS2 nanosheets are grown on nitrogen-doped carbon (NC) coated TiO2 nanotubes to achieve the TiO2 @NC@MoS2 tubular nanostructures. This smart design can effectively shorten the diffusion length of Li+ ions, increase electric conductivity of the electrode, relax volume variation of electrode materials upon cycling, and provide more active sites for electrochemical reactions. Owing to these structural and compositional features, the hierarchical TiO2 @NC@MoS2 nanotubes manifest remarkable lithium storage performance with good rate capability and long cycle life.